2015
DOI: 10.1039/c5gc00077g
|View full text |Cite
|
Sign up to set email alerts
|

One-step extraction and concentration of estrogens for an adequate monitoring of wastewater using ionic-liquid-based aqueous biphasic systems

Abstract: Ethinylestradiol (EE2) is a synthetic hormone that has been recognized as one of the most prominent endocrine disruptors found in the aqueous environment. Nevertheless, the low content of EE2 in wastewater makes its identification/quantification unfeasible - a major drawback for the evaluation of its persistence and environmental impact. In this context, a novel extraction/concentration method for EE2 from wastewater is proposed here based on aqueous biphasic systems composed of ionic liquids (ILs). Aqueous bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
(94 reference statements)
1
36
0
Order By: Relevance
“…However, recent advances have shown that IL-based ABSs are by far more fascinating than these conventional systems due to the possibility of adapting their phase polarities to maximize the partition and selectivity of target compounds 13. Indeed, ABSs composed of ILs proved to lead to complete extractions of the most diverse compounds, in a single-step, by a proper tuning of their chemical structures 1416…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances have shown that IL-based ABSs are by far more fascinating than these conventional systems due to the possibility of adapting their phase polarities to maximize the partition and selectivity of target compounds 13. Indeed, ABSs composed of ILs proved to lead to complete extractions of the most diverse compounds, in a single-step, by a proper tuning of their chemical structures 1416…”
Section: Introductionmentioning
confidence: 99%
“…Cloud points and tie-lines of the ternary systems containing ethyl lactate, water and salt (potassium phosphate, potassium hydrogen phosphate and potassium carbonate) are determined at 298.2 K and 313.2 K. In addition, partition coefficients of L-tryptophan, L-phenylalanine and L-tyrosine between ethyl lactaterich and aqueous phases at two temperatures of 298.2 K and 313.2 K are presented. [28][29], [15]. Obtained cloud points were fitted using the equation given by Merchuk et al [30] to obtain solubility curves:…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous biphasic system (ABS) is recognized as an environmentally friendly method, as an alternative to the traditional LLE, since both phases of the ABS are aqueous solutions, and it could be used for organic compounds [1][2][3][4][5] and biological macromolecule [6][7][8][9] extractions without using any volatile organic solvent. Up to now, ABS could be composed of polymer and salt, polymer and polymer, ionic liquid (IL) and polymer, IL and salt, IL and surfactant.…”
Section: Introductionmentioning
confidence: 99%